CRASHWORTHINESS ANALYSIS OF TRAPEZOID 3D ORIGAMI CRASH STRUCTURE - RAJA, NAVIN (IRC, 2021)
In the modern age of industry revolution 4.0 , the machine development of part and components in various indutries , an increase of part development towards smaller size with high power will be also done .